The cotton (Gossypium hirsutum) NAC transcription factor (FSN1) as a positive regulator participates in controlling secondary cell wall biosynthesis and modification of fibers - Zhang, Jie; Huang, Geng‐Qing; Zou, Dan; Yan, Jing‐Qiu; Li, Yang; Hu, Shan; Li, Xue‐Bao (The New phytologist, 2018)
Cotton (Gossypium hirsutum) fibers are the highly elongated and thickened single-cell trichomes on the seed epidermis. However, little is known about the molecular base of fiber cell wall thickening in detail. In this study, a cotton NAC transcription factor (GhFSN1) that is specifically expressed in secondary cell wall (SCW) thickening fibers was functionally characterized. The GhFSN1 transgenic cotton plants were generated to study how FSN1 regulates fiber SCW formation. Up-regulation of GhFSN1 expression in cotton resulted in an increase in SCW thickness of fibers but a decrease in fiber length. Transcriptomic analysis revealed that GhFSN1 activates or represses numerous downstream genes. GhFSN1 has the ability to form homodimers, binds to its promoter to activate itself, and might be degraded by the ubiquitin-mediated proteasome pathway. The direct targets of GhFSN1 include the fiber SCW-related GhDUF231L1, GhKNL1, GhMYBL1, GhGUT1 and GhIRX12 genes. GhFSN1 binds directly to a consensus sequence (GhNBS), (C/T)(C/G/T)TN(A/T)(G/T)(A/C/G)(A/G)(A/T/G)(A/T/G)AAG, which exists in the promoters of these SCW-related genes. Our data demonstrate that GhFSN1 acts as a positive regulator in controlling SCW formation of cotton fibers by activating its downstream SCW-related genes. Thus, these findings give us novel insights into comprehensive understanding of GhFSN1 function in fiber development.